Implementasi Program I’dād Taḥsīn dan Halaqah Tahfī¨ dalam Menguatkan Hafalan Al-Qur’an Santriwati di Pondok Pesantren Hidayatullah Madiun - Yuli Erawati (BASICA, 2024)
The memorization process often faces various challenges, such as lack of fluency in reading, weak understanding of tajwid, and lack of consistency in maintaining memorization. Realizing this, the Hidayatullah Madiun Islamic Boarding School implemented two main programs, namely I’dād Taḥsīn and Halaqah Tahfī§, as an integrated strategy to strengthen the memorization of the Al-Qur±n of female students. This study aims to (1) analyze the implementation of the I’dād Taḥsīn program in supporting the strengthening of the memorization of the Al-Qur±n of female students, (2) analyze the implementation of the Halaqah Tahfīẓ program in strengthening the memorization of the Al-Qur±n of female students, (3) analyze the supporting and inhibiting factors in the implementation of the I’dād Taḥsīn and Halaqah Tahfīẓ programs at the Hidayatullah Madiun Islamic Boarding School. The method used in this study is a qualitative research method. The approach and type of research used are case studies. Data collection techniques use interviews, observations, and documentation. And the validity of the data uses technical triangulation and source triangulation. The data analysis used is the Miles and Huberman model data analysis. Determination of research subjects using purposive, namely selecting informants who are experts and related to the research, including: caregivers, heads of the tahfidz field, those in charge of halaqah, and female students. The results of this study (1) female students who participated in the I’dād Taḥsīn Program had stronger, more stable and long-lasting memorization. (2) Daily and weekly muroja'ah activities which are part of the Halaqah Tahfīẓ system are very effective in the process of consolidating Al-Qur±n memorization, (3) supporting factors in the implementation of the I’dād Taḥsīn and Halaqah Tahfīẓ programs are full support from the Islamic boarding school, a clear tahfidz curriculum and a Qur'anic environment while inhibiting factors include the busy daily schedule of the Islamic boarding school and the grouping system of the halaqah groups based on the juz chart.